Insulin Glargine in the Treatment of Type 1 and Type 2 Diabetes - Barnett, Anthony H (Dove Medical Press, 2006)
Insulin glargine is an analogue of human insulin that is modified to provide a consistent level of plasma insulin over a long duration. Pharmacokinetic and pharmacodynamic studies show that a single injection of insulin glargine leads to a smooth 24-hour time–action profile with no undesirable pronounced peaks of activity. In clinical trials, this profile has been associated with at least equivalent, if not better, glycemic control than other traditional basal insulins and a significantly lower rate of overall and nocturnal hypoglycemia. The convenience of a once-daily injection, a lack of need for resuspension (insulin glargine is a clear solution when injected), and lower rates of hypoglycemia should translate into improvements in patient treatment satisfaction. This review appraises the evidence for the view that insulin glargine represents an advance in basal insulin therapy for both type 1 and type 2 diabetes patients.